2010
DOI: 10.1124/dmd.109.030155
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9-CYP3A4 Protein-Protein Interactions: Role of the Hydrophobic N Terminus

Abstract: ABSTRACT:Cytochromes P450 (P450s) interact with redox transfer proteins, including P450 reductase (CPR) and cytochrome b 5 (b5), all being membrane-bound. In multiple in vitro systems, P450-P450 interactions also have been observed, resulting in alterations in enzymatic activity. The current work investigated the effects and mechanisms of interaction between CYP2C9 and CYP3A4 in a reconstituted system. CYP2C9-mediated metabolism of S-naproxen and S-flurbiprofen was inhibited up to 80% by coincubation with CYP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 43 publications
4
70
0
Order By: Relevance
“…Experimentally, both hetero-and homodimerization have been shown to affect P450 function. Enzyme kinetic analysis of pairs of P450s, including 2B4/1A4, 2D6/2C9, 2C9/3A4, and 2C9/2C19 has provided evidence that hetero-interactions between the P450s affect the activity of one or both of the P450s in the dimer (Cawley et al, 2001;Hazai and Kupfer, 2005;Subramanian et al, 2009Subramanian et al, , 2010Reed et al, 2010). Homo-oligomerization also has functional consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, both hetero-and homodimerization have been shown to affect P450 function. Enzyme kinetic analysis of pairs of P450s, including 2B4/1A4, 2D6/2C9, 2C9/3A4, and 2C9/2C19 has provided evidence that hetero-interactions between the P450s affect the activity of one or both of the P450s in the dimer (Cawley et al, 2001;Hazai and Kupfer, 2005;Subramanian et al, 2009Subramanian et al, , 2010Reed et al, 2010). Homo-oligomerization also has functional consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Solubilized P450s also have been shown to form homooligomers containing up six or eight protein molecules in some cases, which were mediated by the signal anchor sequence (Von Wachenfeldt and Johnson, 1995). Interactions among P450s may have functional significance because coexpression of a second P450 with a P450 can either inhibit or increase the activity of the first P450 (Cawley et al, 2001;Hazai and Kupfer, 2005;Subramanian et al, 2009Subramanian et al, , 2010Reed et al, 2010). The functional significance of homooligomerization is not clear, but oligomerization of CYP3A4 has been shown to decrease reduction of the P450 by dithionite (Davydov et al, 2005) or the soluble flavin domain of P450BM-3 (Davydov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These complexes are not only observed among P450s and their redox partners: NADPH-cytochrome P450 reductase and cytochrome b 5 (Bridges et al, 1998;Estrada et al, 2013), but also occur between multiple P450 enzymes (Davydov, 2011;. Both homomeric (Davydov et al, 1992;Szczesna-Skorupa et al, 2000;Ozalp et al, 2005;Jamakhandi et al, 2007;Davydov et al, 2010;Hu et al, 2010; and heteromeric (Yamazaki et al, 1997;Backes et al, 1998;Hazai and Kupfer, 2005;Subramanian et al, 2009;Reed et al, 2010;Subramanian et al, 2010) P450-P450 complexes have been reported among several different P450 enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…28 Tracy and coworkers demonstrated that the hydrophobic Nterminus-binding domains of CYP2C9 and CYP3A4 are involved in heterodimer complex formation and truncation of the N-terminus of CYP2C9 led to the abolition of inhibition by CYP3A4. 29 In separate studies, it was hypothesized that the N-terminal domain might be critical for orientation of the protein into the lipid bilayer. 30 Thus, the N-terminus affects the localization on the membrane and can influence orientation and activity.…”
Section: N-terminus Role In Association With Lipid Bilayers Activitymentioning
confidence: 99%